Multi-coated modified positive electrode material, positive electrode sheet and secondary battery

CN123017946APending Publication Date: 2026-10-30HEFEI GUOXUAN HIGH TECH POWER ENERGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611382950.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本申请的主要目的在于提供一种多重包覆改性正极材料、正极极片及二次电池,以解决现有技术中正极材料循环稳定性差的问题

Benefits of technology

[0042]为使本申请实施例的目的、技术方案和优点更加清楚,下面将对本申请实施例中的技术方案进行清楚、完整地描述。实施例中未注明具体条件者,按照常规条件或制造商建议的条件进行。所用试剂或仪器未注明生产厂商者,均为可以通过市售购买获得的常规产品。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a multiple-coated modified positive electrode material, a positive electrode sheet and a secondary battery, and relates to the technical field of secondary batteries. The positive electrode material comprises a core and a shell layer. The core comprises a positive electrode active material, and the shell layer comprises multiple coating layers. The thickness of each coating layer is independently 1nm-50nm, and each coating layer independently comprises one of a first material, a second material, a third material and a fourth material. The materials of the two coating layers are different. The first material comprises niobium silicon aluminates, niobium silicates, niobium aluminates, aluminum silicates, lithiumated niobium silicon aluminates and lithiumated salts of the above-mentioned salts. The second material comprises at least one of lithium-containing oxygen acid salts, phosphate salts and conductive polymers. The third material comprises at least one of oxides, oxyfluorides and oxynitrides of at least one of aluminum, niobium, titanium, zirconium, tungsten and boron. The fourth material comprises at least one of oxides of silicon, nitrides of silicon, silicon oxynitride and carbides of silicon. The positive electrode material has good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of secondary battery technology, and more specifically, to a multi-coated modified cathode material, a cathode sheet, and a secondary battery. Background Technology

[0002] Lithium-ion battery cathode materials (such as high-nickel layered oxide lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, etc., lithium-rich layered spinel structure oxide lithium nickel manganese oxide, etc.) typically face the following problems under high voltage, high temperature, or high rate conditions:

[0003] Severe interfacial side reactions occur, such as electrolyte oxidation and decomposition under high voltage, and HF production from LiPF6 decomposition, leading to transition metal dissolution, surface structure reconstruction, and increased impedance; microcracks and structural degradation occur in particles, with stress accumulation during cycling triggering microcracks, and electrolyte penetration accelerating interfacial corrosion; impedance growth and intensified polarization also occur. Currently, no suitable method has been found to solve the above problems of cathode materials. Summary of the Invention

[0004] The main objective of this application is to provide a multi-coated modified cathode material, cathode sheet, and secondary battery to solve the problem of poor cycle stability of cathode materials in the prior art.

[0005] To achieve the above objectives, according to a first aspect of this application, a multi-coated modified cathode material is provided, comprising a core and a shell. The core comprises a cathode active material, and the shell comprises N coating layers, where N is an integer between 2 and 4. The shell comprises a first coating layer and a second coating layer, and the first and second coating layers are sequentially stacked from the inside to the outside along the radial direction of the core. The thickness of each coating layer is independently 1 nm to 50 nm.

[0006] The first coating layer and the second coating layer each independently include one of the first material, the second material, the third material, and the fourth material, and the materials of the first coating layer and the second coating layer are different;

[0007] The first material includes at least one of niobium aluminosilicate, niobium silicate, niobium aluminate, aluminosilicate, lithium-modified niobium aluminosilicate, lithium-modified niobium silicate, lithium-modified niobium aluminate, and lithium-modified aluminosilicate.

[0008] The second material includes at least one of lithium oxyacid salts, phosphates, and conductive polymers;

[0009] The third material includes at least one oxide, oxyfluoride, or nitrogen oxide selected from aluminum, niobium, titanium, zirconium, tungsten, and boron;

[0010] The fourth material includes at least one of silicon oxide, silicon nitride, silicon oxynitride, and silicon carbide.

[0011] Setting multiple coating layers helps to form a good barrier between the positive electrode active material and the electrolyte, reducing side reactions between the electrolyte and the positive electrode active material, reducing the dissolution of transition metals. At the same time, different coating layers have different functions and also help to balance the cycle performance and kinetic performance of the multi-coated modified positive electrode material.

[0012] Furthermore, the oxyacid salts of lithium include at least one of lithium phosphate, lithium aluminate, and lithium borate.

[0013] The aforementioned lithium oxyacid salts exhibit good structural stability and ionic conductivity, which helps to improve the cycle performance and kinetic performance of multi-coated modified cathode materials.

[0014] Furthermore, phosphates include ammonium metaphosphate.

[0015] The aforementioned phosphates can react with HF during cycling to form stable phosphates, thereby consuming HF, protecting the positive electrode active material from corrosion, helping to reduce transition metal dissolution, and extending battery cycle life.

[0016] Furthermore, the conductive polymer includes poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS).

[0017] The aforementioned conductive polymers help provide a more uniform and stable transport channel for lithium ions, which in turn helps reduce polarization and improve the cycle performance, first coulombic efficiency, and kinetic performance of multi-coated modified cathode materials.

[0018] Furthermore, the third material includes at least one of alumina, niobium oxide, zirconium oxide, titanium oxide, and titanium oxynitride.

[0019] The aforementioned third material has good mechanical strength, which helps to suppress the propagation of microcracks caused by volume changes in the positive electrode active material during charging and discharging, thereby helping to improve the cycle performance of the multi-coated modified positive electrode material.

[0020] Furthermore, the general chemical formula for silicon oxide is SiO₂. x Where 0 < x ≤ 2; the general chemical formula of silicon nitrides is SiN. y , where 0.7 < y < 1.2; the carbide of silicon is SiC.

[0021] The aforementioned silicon oxides, silicon nitrides, and silicon carbides exhibit good chemical stability and can form a physical barrier between the positive electrode active material and the electrolyte, thereby helping to suppress electrolyte decomposition and improve the cycle stability of batteries using this multi-coated modified positive electrode material.

[0022] Furthermore, the first material is at least one of a nanocrystalline phase and an amorphous phase.

[0023] Controlling the crystal form of the first material helps to further reduce the interfacial charge transfer resistance, optimize lithium-ion transport performance, and improve the cycle performance and kinetic performance of the multi-coated modified cathode material.

[0024] Furthermore, the thickness of the shell is 2nm~200nm.

[0025] Adjusting the shell thickness within the above range helps to balance the cycle stability and specific capacity of multi-coated modified cathode materials, thereby improving the overall electrochemical performance of multi-coated modified cathode materials.

[0026] Furthermore, when N=2, the second coating layer includes the first material, and the first coating layer includes at least one of the second material, the third material, and the fourth material.

[0027] When N=2, controlling the second coating layer to include the first material, i.e., the outermost layer including the first material, helps to significantly improve the transport performance of lithium ions in the shell, and also helps to suppress side reactions between the electrolyte and the positive electrode active material, thereby helping to improve the cycle stability and kinetic performance of the multi-coated modified positive electrode material.

[0028] Furthermore, the first coating layer includes at least one of a second material and a third material.

[0029] This application has found through experiments that the first coating layer, including a second or third material, has a more significant effect on improving the cycle performance of the multi-coated modified cathode material.

[0030] Furthermore, the shell also includes a third covering layer, with the second covering layer located between the first and third covering layers. The third covering layer includes any one of the first, second, third, and fourth materials, and the materials of the third, first, and second covering layers are different.

[0031] Increasing the number of coating layers in the shell helps improve the structural stability and ion transport performance of multi-coated modified cathode materials, thereby enhancing their cycle stability and specific capacity.

[0032] Furthermore, when N=3, the first coating layer includes a third or fourth material, the second coating layer includes a fourth or second material, and the third coating layer includes a first material; and the materials of the first and second coating layers are different.

[0033] The third coating layer, also known as the outermost layer, includes the first material, which helps optimize the lithium-ion transport path, improve lithium-ion transport performance, and enhance the kinetic performance of the multi-coated modified cathode material. In addition, it helps reduce interfacial impedance, enabling the battery using this multi-coated modified cathode material to form a thin and uniform CEI film during the first cycle. This helps to further optimize the cycle stability and first coulombic efficiency of the multi-coated modified cathode material, and also helps to reduce capacity loss and improve the specific capacity of the multi-coated modified cathode material.

[0034] Furthermore, the shell also includes a fourth covering layer, with a third covering layer located between the second and fourth covering layers. The third covering layer includes a first material, and the fourth covering layer includes any one of the second, third, and fourth materials, and the material of the fourth covering layer is different from the materials of the first, second, and third covering layers.

[0035] The shell layer includes a fourth coating layer, meaning it contains four materials. This allows for the full utilization of the properties of each material. For example, the third and fourth materials can be used to improve the mechanical strength and structural stability of the multi-coated modified cathode material, thereby enhancing its cycle performance. The second material can significantly improve the electronic or ionic conductivity of the multi-coated modified cathode material, further improving its cycle performance. Additionally, the first material can provide multiple ion transport channels for lithium ions, further enhancing ion diffusion performance and improving the kinetic performance of the multi-coated modified cathode material. Furthermore, the use of multiple coating layers helps avoid the adverse effects of a single coating layer on the capacity or kinetic performance of the multi-coated modified cathode material, contributing to a balanced overall electrochemical performance.

[0036] Furthermore, when N=4, the first coating layer includes a third material, the second coating layer includes a fourth material, the third coating layer includes a first material, and the fourth coating layer includes a second material.

[0037] This application demonstrates through experiments that the above-mentioned regulation of multi-coated materials helps to further improve the cycle stability of multi-coated modified cathode materials and broaden their application range.

[0038] Furthermore, each of the N coating layers is independently prepared using at least one of atomic layer deposition, chemical vapor deposition, chemical reaction, and chemical impregnation methods. Specifically, when the coating layer includes a first material, it is prepared using a chemical reaction method; when the coating layer includes a second material, it is prepared using at least one of chemical impregnation and atomic layer deposition methods; when the coating layer includes a third material, it is prepared using atomic layer deposition; and when the coating layer includes a fourth material, it is prepared using chemical vapor deposition.

[0039] Experiments revealed that different preparation methods for materials have a significant impact on their performance. The above-mentioned selection of preparation methods for each material is beneficial to improving the uniformity of the coating layer, maximizing the performance of each material, and effectively improving the cycle performance of multi-coated modified cathode materials.

[0040] According to a second aspect of this application, a positive electrode sheet is provided, which includes the multi-coated modified positive electrode material of the first aspect of this application. Because it includes the aforementioned multi-coated modified positive electrode material, the positive electrode sheet also exhibits good cycle stability.

[0041] According to a third aspect of this application, a secondary battery is provided, which includes the aforementioned positive electrode. Due to the inclusion of the aforementioned positive electrode, the secondary battery has excellent cycle stability. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0043] As described in the background section of this application, existing technologies suffer from the problem that cathode materials often lack both good cycle stability and specific capacity. To address this issue, in a typical embodiment of this application, a multi-coated modified cathode material is provided, comprising a core and a shell. The core includes a cathode active material, and the shell comprises N coating layers, where N is an integer between 2 and 4. The shell includes a first coating layer and a second coating layer, which are sequentially stacked from the inside to the outside along the radial direction of the core. The thickness of each coating layer is independently 1 nm to 50 nm.

[0044] The first coating layer and the second coating layer each independently include one of the first material, the second material, the third material, and the fourth material, and the materials of the first coating layer and the second coating layer are different;

[0045] The first material includes at least one of niobium aluminosilicate, niobium silicate, niobium aluminate, aluminosilicate, lithium-modified niobium aluminosilicate, lithium-modified niobium silicate, lithium-modified niobium aluminate, and lithium-modified aluminosilicate.

[0046] The second material includes at least one of lithium oxyacid salts, phosphates, and conductive polymers;

[0047] The third material includes at least one oxide, oxyfluoride, or nitrogen oxide selected from aluminum, niobium, titanium, zirconium, tungsten, and boron;

[0048] The fourth material includes at least one of silicon oxide, silicon nitride, silicon oxynitride, and silicon carbide.

[0049] In the above embodiments of this application, the coating layer helps to suppress side reactions between the positive electrode active material and the electrolyte, reduce reactivity, and improve the cycle stability of the multi-coated modified positive electrode material. Specifically, at least two coating layers, a first coating layer and a second coating layer, are provided, and each coating layer is selected from one of a first material, a second material, a third material, and a fourth material. Furthermore, the two coating layers are made of different materials, which helps to optimize the cycle stability and reduce the interfacial resistance of the multi-coated modified positive electrode material using different materials, thereby improving the overall electrochemical performance of the multi-coated modified positive electrode material. Specifically, the first material helps to improve the ionic conductivity of the shell, reduce polarization, and decrease electrolyte decomposition, enabling the multi-coated modified positive electrode material to form a thin and uniform CEI film (positive electrode electrolyte interface film) during cycling, thereby improving the specific capacity and initial coulombic efficiency of the multi-coated modified positive electrode material. When the second material is an oxoacid salt of lithium, it helps to suppress the dissolution of transition metal ions, prevent electrolyte decomposition, and further enhance structural stability. When the second material is a phosphate, it helps to suppress the dissolution of transition metals and significantly improves the cycle performance of the battery. When the second material is a conductive polymer, it can form a highly conductive path on the surface of the positive electrode active material, significantly improving the discharge specific capacity under high current, while also helping to isolate the positive electrode active material from the electrolyte, reducing interfacial impedance, and extending cycle life. The third or fourth material helps to optimize the structural stability and electrochemical stability of the multi-coated modified positive electrode material, further improving the cycle stability of the multi-coated modified positive electrode material. This application, by further controlling the thickness of each coating layer in the multi-coated modified positive electrode material, helps to ensure that the performance of each coating layer is maximized, while not affecting ion transport or reducing the specific capacity of the multi-coated modified positive electrode material, thus helping to improve the overall electrochemical performance of the multi-coated modified positive electrode material.

[0050] Specifically, but not limitingly, the thickness of each coating layer is independently any value within the range of 1 nm, 2 nm, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, or any two of the above values.

[0051] In the description of this application, thickness refers to the average thickness, which is measured using a transmission electron microscope.

[0052] Specifically, but not limitingly, in this application, the positive electrode active material includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium nickel manganese oxide.

[0053] In some embodiments, the oxyacid salts of lithium include at least one of lithium phosphate, lithium aluminate, and lithium borate.

[0054] In the above embodiments of this application, the oxoacid salt of lithium has good structural stability and good lithium-ion conduction performance, which helps to reduce charge transfer resistance and significantly improve rate performance; in addition, it also helps to block the contact between the positive electrode active material and the electrolyte, inhibit the dissolution of transition metal ions, and further improve the cycle stability of the multi-coated modified positive electrode material.

[0055] In some implementations, the phosphate includes ammonium metaphosphate.

[0056] In the above embodiments of this application, phosphate can react with HF during cycling to form stable phosphate, thereby consuming HF, protecting the positive electrode active material from corrosion, helping to reduce the dissolution of transition metals, and extending the battery cycle life.

[0057] In some embodiments, the conductive polymer includes poly(3,4-ethylenedioxythiophene):polystyrene sulfonate.

[0058] In the above embodiments of this application, the conductive polymer has good electronic conductivity, which helps to build a highly conductive flexible network on the surface of the positive electrode active material, improves electron transport efficiency, reduces contact resistance and charge transfer resistance, improves rate performance, and also helps to form a good isolation film between the positive electrode active material and the electrolyte. This helps to suppress transition metal dissolution, electrolyte oxidative decomposition and HF corrosion, reduce capacity decay caused by side reactions, and improve the cycle performance, specific capacity and rate performance of the multi-coated modified positive electrode material, thereby enhancing the overall electrochemical performance of the positive electrode material.

[0059] In some embodiments, the third material includes at least one of alumina, niobium oxide, zirconium oxide, titanium oxide, and titanium oxynitride.

[0060] In the above embodiments of this application, the third material has good mechanical strength, which helps to suppress the propagation of microcracks caused by changes in charge and discharge volume, thereby improving the cycle stability of the multi-coated modified cathode material.

[0061] In some embodiments, the general chemical formula of silicon oxide is SiO. x Where 0 < x ≤ 2; the general chemical formula of silicon nitrides is SiN. y , where 0.7 < y < 1.2; the carbide of silicon is SiC.

[0062] In the above embodiments of this application, the material has good chemical stability, which helps to form a physical barrier between the positive electrode active material and the electrolyte, thereby helping to suppress electrolyte decomposition and improve the cycle stability of the battery using the multi-coated modified positive electrode material.

[0063] In some embodiments, the first material is at least one of a nanocrystalline phase and an amorphous phase.

[0064] In the above embodiments of this application, when the first material is at least one of a nanocrystalline phase or an amorphous phase, it helps to reduce the interfacial charge transfer resistance, significantly improve the ion transport performance, and significantly improve the kinetic performance while improving the cycle stability of the multi-coated modified cathode material.

[0065] In some implementations, the thickness of the shell is 2nm to 200nm.

[0066] In the above embodiments of this application, controlling the thickness of the shell within the above range helps to balance the protective effect of the shell on the core of the positive electrode active material and the ion transport performance, ensuring that the multi-coated modified positive electrode material has good cycle stability, rate performance and specific capacity.

[0067] Specifically, but not limitingly, the thickness of the shell can be any value within the range of 2nm, 5nm, 10nm, 20nm, 50nm, 70nm, 100nm, 130nm, 150nm, 180nm, 200nm, or any two of the above values, without any special limitation.

[0068] In some implementations, when N=2, the second coating layer includes the first material, and the first coating layer includes at least one of the second material, the third material, and the fourth material.

[0069] In the above embodiments of this application, when N=2, controlling the second coating layer, that is, the outermost layer, to include the first material helps to maximize the ion diffusion performance, providing multiple channels for the transport of lithium ions in the multi-coated modified cathode material, thereby helping to significantly improve the kinetic performance of the multi-coated modified cathode material, reduce polarization, fully utilize the capacity of the cathode active material, and improve the specific capacity and cycle stability of the multi-coated modified cathode material.

[0070] In some embodiments, the first covering layer includes at least one of a second material and a third material.

[0071] In the above embodiments of this application, this application has found through experiments that when the first coating layer includes a second material or a third material, the cycle stability of the multi-coated modified cathode material is significantly better than when the first coating layer includes a fourth material.

[0072] In some embodiments, the shell further includes a third covering layer, with the second covering layer located between the first and third covering layers. The third covering layer includes any one of the first, second, third, and fourth materials, and the materials of the third, first, and second covering layers are different.

[0073] In the above embodiments of this application, the shell layer, including the third coating layer, can be made of a variety of materials. Selecting any three of the above four materials can help improve the structural stability and ion transport performance of the multi-coated modified cathode material, and enhance the cycle stability and specific capacity of the multi-coated modified cathode material.

[0074] In some implementations, when N=3, the first coating layer includes a third or fourth material, the second coating layer includes a fourth or second material, and the third coating layer includes a first material; and the materials of the first coating layer and the second coating layer are different.

[0075] In the above embodiments of this application, the third coating layer, i.e. the outermost layer, including the first material, helps to optimize the lithium-ion transport path, improve lithium-ion transport performance, and improve the kinetic performance of the multi-coated modified cathode material. In addition, it also helps to reduce the interface impedance, enabling the battery using the multi-coated modified cathode material to form a thin and uniform CEI film during the first cycle, which helps to further optimize the cycle stability and first coulombic efficiency of the multi-coated modified cathode material, and helps to reduce capacity loss and improve the specific capacity of the multi-coated modified cathode material.

[0076] In some embodiments, the shell further includes a fourth covering layer, with the third covering layer located between the second and fourth covering layers. The third covering layer includes a first material, and the fourth covering layer includes any one of the second, third, and fourth materials, and the material of the fourth covering layer is different from the materials of the first, second, and third covering layers.

[0077] In the above embodiments of this application, the shell layer includes a fourth coating layer, that is, the shell layer contains four materials, which can give full play to the performance of each material. For example, on the one hand, the third and fourth materials can be used to improve the mechanical strength of the multi-coated modified cathode material and improve the structural stability of the multi-coated modified cathode material, thereby helping to improve the cycle performance of the multi-coated modified cathode material; on the other hand, the second material can be used to significantly improve the electronic conductivity or ionic conductivity of the multi-coated modified cathode material, thereby helping to improve the cycle performance of the multi-coated modified cathode material; in addition, the first material can be used to provide multiple ion transport channels for lithium ion transport, further improving ion diffusion performance and improving the kinetic performance of the multi-coated modified cathode material; in addition, setting multiple coating layers helps to avoid the adverse effects of a single coating layer on the capacity or kinetic performance of the multi-coated modified cathode material, and helps to balance the comprehensive electrochemical performance of the multi-coated modified cathode material.

[0078] In some implementations, when N=4, the first coating layer includes a third material, the second coating layer includes a fourth material, the third coating layer includes a first material, and the fourth coating layer includes a second material.

[0079] In the above embodiments of this application, by screening the materials of each coating layer, it is helpful to further optimize the cycle stability of the multi-coated modified cathode material and broaden the application range of the multi-coated modified cathode material.

[0080] In some embodiments, the N coating layers are each independently prepared using at least one of atomic layer deposition, chemical vapor deposition, chemical reaction, and chemical impregnation. Specifically, when the coating layer includes a first material, it is prepared using a chemical reaction; when the coating layer includes a second material, it is prepared using at least one of chemical impregnation and atomic layer deposition; when the coating layer includes a third material, it is prepared using atomic layer deposition; and when the coating layer includes a fourth material, it is prepared using chemical vapor deposition.

[0081] In the above embodiments of this application, experiments have shown that different preparation methods of materials have a significant impact on their performance. The above selection of preparation methods for each material is beneficial to improving the uniformity of the coating layer, maximizing the performance of each material, and effectively improving the cycle performance of the multi-coated modified cathode material.

[0082] Specifically, but not limitingly, the steps for preparing a first material, such as niobium aluminosilicate, using a chemical reaction method include:

[0083] Niobium salt, silicon salt, and aluminum salt are mixed with a solvent to obtain a first mixture; the molar ratio of niobium, silicon, and aluminum in the first mixture is (1~2):(1~2):1;

[0084] Complexing agents such as citric acid, oxalic acid, and acetylacetone are mixed with the first mixture, and the total molar ratio of the complexing agent to the metal salt is controlled to be (1~2):1. The pH value of the system is adjusted to 4~5.5, a complexing reaction occurs, and the mixture is dried and calcined to obtain niobium aluminosilicate.

[0085] After the above drying process is completed, lithium salt is added and then calcined to obtain lithiated niobium aluminosilicate.

[0086] In addition, niobium aluminosilicates can also be prepared by spray drying: niobium source, silicon source, aluminum source and solvent are mixed, spray dried, and calcined to obtain niobium aluminosilicates.

[0087] For aluminosilicates, aluminosilicates and their lithiated salts, the above method can be used for preparation.

[0088] In another typical embodiment of this application, a positive electrode sheet is provided, which includes the multi-coated modified positive electrode material described in the above embodiments of this application. Due to the inclusion of the aforementioned multi-coated modified positive electrode material, this positive electrode sheet also exhibits good cycle stability, kinetic performance, and capacity.

[0089] In another typical embodiment of this application, a secondary battery is provided, which includes the positive electrode sheet in the above embodiments of this application. Because it includes the positive electrode sheet, the secondary battery has excellent comprehensive electrochemical performance.

[0090] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0091] Example 1

[0092] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0093] 100g of NCM811 (D50 is 10μm) was placed in a fluidized bed atomic layer deposition apparatus and atomic layer deposition was performed at 150℃ using trimethylaluminum (TMA) and H2O as precursors. Cyclic deposition was carried out to make the thickness of the first alumina coating layer 3nm, and the first intermediate product was obtained.

[0094] The first intermediate product was transferred into a chemical vapor deposition reactor, and tetraethyl orthosilicate (TEOS) vapor (TEOS: 1.0 g / min) along with a carrier gas and an oxidizing gas (oxygen: 1000 sccm; nitrogen: 5000 sccm) was introduced at 520°C. Deposition was carried out for 40 min to form a second SiO2 coating layer with a thickness of 10 nm, thus obtaining the second intermediate product.

[0095] The second intermediate product was added to an 800 mL mixed solution of ethanol and deionized water in a volume ratio of 7:3. Then, Nb(OC2H5)5, TEOS, and Al(NO3)3·9H2O were added sequentially, with a molar ratio of Nb, Si, and Al of 1:2:1. The total amount of metal salts (Nb(OC2H5)5 and Al(NO3)3·9H2O) was 0.8 wt% of the second intermediate product. Citric acid was then added, with a molar ratio of citric acid to the total molar amount of Nb and Al in the metal salts of 1.2:1. The pH of the system was then adjusted to 4.5 using ammonia. After stirring at 40°C for 2 h, the temperature was raised to 60°C for slow hydrolysis and condensation for 1 h, forming a film on the surface of the second intermediate product in situ. The film was filtered, washed, dried at 80°C for 12 h, and then kept at 700°C for 3 h in air to obtain a third coating layer of niobium aluminosilicate with a thickness of 25 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0096] Example 2

[0097] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0098] Take NCA (LiNi) 0.8 Co 0.15 Al 0.05 O2, D 50 100g of niobium oxide (9 μm) was placed in a fluidized bed atomic layer deposition apparatus and atomic layer deposition was performed at 180°C using NbCl5 and H2O as precursors. Cyclic deposition was carried out to make the thickness of the first niobium oxide coating layer 4nm, and the first intermediate product was obtained.

[0099] The first intermediate product was added to a 1 L mixed solution of ethanol and water in a volume ratio of 8:2. Then, Nb(OC2H5)5, TEOS and Al(NO3)3·9H2O were added sequentially, with the molar ratio of Nb, Si and Al being 1.5:1:1. The total amount of metal salts (Nb(OC2H5)5 and Al(NO3)3·9H2O) was 1.0 wt% of the first intermediate product. Citric acid was then added, with the molar ratio of citric acid to the total molar amount of Nb and Al in the metal salts being 1:1. The pH of the system was then adjusted to 5.0 with ammonia. The mixture was stirred at 60 °C for 3 h, filtered and washed, and dried at 80 °C for 10 h to obtain the precursor.

[0100] The precursor was mixed with LiOH·H2O (the total molar ratio of lithium salt to the aforementioned Nb and Al elements was 1.05:1), placed in a tube furnace, and then kept at 650°C for 5 hours under a nitrogen atmosphere to obtain a second coating layer of lithiated niobium aluminosilicate amorphous phase with a thickness of 30 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0101] Example 3

[0102] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0103] Take NCM90 (LiNi) 0.9 Co 0.05 Mn 0.05 O2, D 50 100g of alumina (8 μm) was placed in a fluidized bed atomic layer deposition apparatus and atomic layer deposition was performed at 130°C using TMA and H2O as precursors. The deposition was repeated to make the thickness of the first alumina coating layer 4nm, thus obtaining the first intermediate product.

[0104] The first intermediate product was transferred to a chemical vapor deposition reactor, and SiH4, N2O and NH3 (volume ratio of 1:3:2) were introduced at 480°C. Deposition was carried out for 60 min to form a second coating layer of silicon oxynitride with a thickness of 10 nm, thus obtaining the second intermediate product.

[0105] The second intermediate product was added to a 1.2 L mixed solution of ethanol and water in a volume ratio of 6:4. NbCl5, tetraethyl orthosilicate, and aluminum isopropoxide were added sequentially, with the molar ratio of Nb, Si, and Al being 1:2:1. The total amount of metal salts (NbCl5 and aluminum isopropoxide) was 1.2 wt% of the second intermediate product. Oxalic acid was then added, with the molar ratio of oxalic acid to the total molar amount of Nb and Al in the metal salts being 1.2:1. The pH of the system was then adjusted to 4.0 with ammonia. The mixture was stirred at 50 °C for 3 h to form a film on the surface of the first intermediate product in situ. The film was filtered, washed, and dried at 100 °C for 10 h. Subsequently, it was heat-treated in air at 400 °C for 4 h to form a third coating layer of niobium aluminosilicate with a thickness of 25 nm, thus obtaining the third intermediate product.

[0106] The third intermediate product was immersed in a 0.1 mol / L ammonium dihydrogen phosphate solution, stirred for 1 h, filtered, dried at 120 °C, and then heat-treated in air at 450 °C for 2 h to form a fourth ammonium metaphosphate coating layer with a thickness of 8 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0107] Example 4

[0108] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0109] Lithium-rich layered cathode material Li 1.2 Mn 0.6 Ni 0.2 O2 (D) 50 100g of a niobium aluminosilicate (12 μm) was added to a 1.5L mixed solution containing NbCl5, TEOS, and aluminum isopropoxide in a volume ratio of 7:3 of ethanol and water, wherein the molar ratio of Nb, Si, and Al was 1:1.5:1, and the total metal salt (NbCl5 and aluminum isopropoxide) was 1.5wt% of the cathode material. Citric acid was then added, with the molar ratio of citric acid to the total molar amount of Nb and Al in the metal salt being 1.5:1. The pH of the system was then adjusted to 4.5 with ammonia, and the mixture was stirred at 70°C for 3 hours to form a film on the surface of the first intermediate product in situ. The film was filtered, washed, and dried at 90°C for 12 hours. Subsequently, the film was heat-treated in air at 500°C for 3 hours to form a first coating layer of niobium aluminosilicate with a thickness of 28nm, thus obtaining the first intermediate product.

[0110] The first intermediate product was placed in a fluidized bed atomic layer deposition apparatus, and a second coating layer ZrO2 with a thickness of 6 nm was deposited at 180 °C using ZrCl4 and H2O as precursors to obtain the second intermediate product.

[0111] The second intermediate product was placed in a chemical vapor deposition reactor, and SiH4 and NH3 (volume ratio 1:4) were introduced at 460°C for 50 min to form a third SiN coating layer with a thickness of 9 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0112] Example 5

[0113] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0114] Take spinel LNMO cathode material powder (LiNi) 0.5 Mn 1.5 O4, D 50 100g of amorphous SiO2 (5 μm) was placed in a chemical vapor deposition reactor, and hexamethyldisiloxane (HMDSO) and O2 (volume ratio 1:5) were introduced at 520℃ for 45 min to form amorphous SiO2. 1.7 The first coating layer has a thickness of 15 nm, and the first intermediate product is obtained.

[0115] The first intermediate product was added to a 1L ethanol solution containing Nb(OC2H5)5, TEOS, and Al(NO3)3, wherein the molar ratio of Nb, Si, and Al was 2:1:1, and the total amount of metal salts (Nb(OC2H5)5 and Al(NO3)3) was 1.0 wt% of the first intermediate product. Then, acetylacetone was added, with the molar ratio of acetylacetone to the total molar amount of Nb and Al in the metal salts being 2:1. The pH of the system was then adjusted to 5.5 with ammonia, stirred at 60°C for 2 hours, filtered and washed, dried at 80°C for 12 hours, and uniformly mixed with Li2CO3 (the molar ratio of Li to the total molar amount of Nb and Al was 1.1:1). The mixture was then heat-treated in air at 700°C for 6 hours to form a lithiated niobium aluminosilicate second coating layer with a thickness of 25 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0116] Example 6

[0117] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0118] Take NCM90 (LiNi) 0.9 Co 0.05 Mn 0.05 O2, D 50 100g of alumina (8 μm) was placed in a fluidized bed atomic layer deposition apparatus and atomic layer deposition was performed at 120°C using TMA and H2O as precursors. The deposition was repeated to make the thickness of the first alumina coating layer 4nm, thus obtaining the first intermediate product.

[0119] The first intermediate product was transferred into a chemical vapor deposition reactor, and a second coating layer of SiO2 was deposited at 500°C with TEOS and O2 (volume ratio of 1:8) for 40 min and a thickness of 10 nm to obtain the second intermediate product.

[0120] The second intermediate product was placed in a mixed solution containing niobium source, silicon source and aluminum source (where the niobium source is Nb(OC2H5)5, the silicon source is tetraethyl orthosilicate (TEOS), and the aluminum source is Al(NO3)3·9H2O). The solvent of the mixed solution was water and ethanol, with a volume ratio of water to ethanol of 1:1 (the pH value of the mixed system containing salt is 5). The molar ratio of Nb, Si and Al was 1:2:1. The mixture was reacted in a high-pressure reactor at 180°C for 6 hours. After filtration, washing and drying, the mixture was sintered in air at 600°C for 4 hours to form a nanocrystalline niobium aluminosilicate third coating layer with a thickness of 18 nm, thus obtaining the third intermediate product.

[0121] The third intermediate product was immersed in a 0.15 mol / L diammonium hydrogen phosphate solution, stirred for 2 hours, filtered, dried at 100°C, and heat-treated in air at 450°C for 3 hours to form a fourth lithium phosphate coating layer with a thickness of 6 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0122] Example 7

[0123] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0124] Take NCA (LiNi) 0.8 Co 0.15 Al 0.05 O2, D 50 100g of silicon oxynitride (with a thickness of 9 μm) was placed in a chemical vapor deposition reactor, and SiH4, N2O and NH3 (volume ratio of 1:3:1.5) were introduced at 460℃. After deposition for 55 min, the first coating layer of silicon oxynitride with a thickness of 12nm was formed, and the first intermediate product was obtained.

[0125] The first intermediate product was transferred into a fluidized bed atomic layer deposition apparatus, and a second coating layer of TiO2 with a thickness of 5 nm was deposited at 160°C using TiCl4 and H2O to obtain the second intermediate product.

[0126] The second intermediate product was added to a 1L mixed solution containing NbCl5 and Al(NO3)3 in a volume ratio of water and ethanol of 1:1, wherein the molar ratio of Nb to Al was 2:1, and the total amount of metal salt added was 0.8wt% of the second intermediate product. The pH of the system was adjusted to 6.0 with ammonia, and the mixture was stirred at 60°C for 3 hours. After filtration, washing, and drying, the mixture was mixed with LiNO3 (the molar ratio of Li to the aforementioned Nb and Al was 1.05:1), and heat-treated in air at 550°C for 5 hours to form a third coating layer of 20nm thick niobium-aluminum alloy salt, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0127] Example 8

[0128] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0129] 100g of NCM811 (D50 is 10μm) was placed in a fluidized bed atomic layer deposition apparatus and atomic layer deposition was performed at 200℃ using tris(dimethylamino)borane and H2O2 as precursors. The first coating layer, LiBO2 ion conductor layer, with a thickness of 6nm was formed by cyclic deposition, and the first intermediate product was obtained.

[0130] The first intermediate product was placed in a spray drying apparatus, using a mixed solution containing niobium source, silicon source and aluminum source as the precursor liquid, wherein the niobium source was NbCl5, the silicon source was tetraethyl orthosilicate, the aluminum source was Al(NO3)3·9H2O, the molar ratio of Nb, Si and Al was 1:1:1, the total concentration of metal ions was 0.5 mol / L, the solvent of the mixed solution was ethanol and water, the volume ratio of ethanol to water was 1:1, the feed rate was 5 mL / min, the inlet temperature was 220℃, and the outlet temperature was 120℃, to obtain precursor-coated powder. The precursor-coated powder was directly pyrolyzed in air at 620℃ for 2 h to form a second coating layer of niobium aluminosilicate with a thickness of 30 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0131] Example 9

[0132] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0133] Take 100g of lithium iron phosphate cathode material (D50 is 6μm), place it in a chemical vapor deposition reactor, introduce HMDSO and O2 (volume ratio is 1:6) at 480℃, and deposit for 50min to form an amorphous SiO2 first coating layer with a thickness of 10nm, and obtain the first intermediate product.

[0134] The first intermediate product was transferred into a fluidized bed atomic layer deposition apparatus and deposited at 180°C using trimethylaluminum as a precursor, lithium tert-butanol (LiOtBu) and trimethylaluminum (TMA) as precursors, and H2O as a co-reactant. The deposition was carried out in an alternating manner of LiOtBu and TMA cycles (the ratio of LiOtBu to TMA cycles was 1:1) to form a second coating layer of lithium aluminate (LiAlO2) with a thickness of 5 nm, thus obtaining the second intermediate product.

[0135] The second intermediate product was added to a 1L mixed solution containing NbCl5, tetraethyl orthosilicate, and aluminum isopropoxide in a volume ratio of 7:3 of ethanol and water, wherein the molar ratio of Nb, Si, and Al was 1:1:1, and the total amount of metal salts added was 1.2wt% of the mass of the second intermediate product. Citric acid was added, with a molar ratio of citric acid to Nb and Al of 2:1. The pH was adjusted to 5.0 using ammonia. The mixture was stirred at 60°C for 3 hours, filtered, washed, and dried. It was then mixed with Li2CO3 (with a molar ratio of Li to the aforementioned Nb and Al of 1.1:1) and heat-treated at 600°C for 4 hours under a nitrogen atmosphere to form a lithiated lithium niobium aluminosilicate amorphous phase third coating layer with a thickness of 20nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0136] Example 10

[0137] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0138] Lithium-rich manganese-based cathode materials (Li 1.2 Mn 0.6 Ni 0.2 O2, D 50 100g of TiO2 (11μm) was placed in a plasma-enhanced atomic layer deposition apparatus and cyclically deposited at 150°C using TiCl4 and NH3 as precursors to form a TiO2 layer with a thickness of 5nm. 0.3 N 0.9 The first coating layer yields the first intermediate product;

[0139] The first intermediate product was transferred to a chemical vapor deposition reactor, and SiH4 and CH4 (volume ratio of 1:4) were introduced at 600°C for 30 min to form an amorphous SiC second coating layer with a thickness of 8 nm, thus obtaining the second intermediate product.

[0140] The second intermediate product was added to an ethanol solution containing Nb(OC2H5)5, TEOS and Al(NO3)3, wherein the molar ratio of Nb, Si and Al was 2:1:1 and the total amount of metal salts added was 1.0 wt% of the second intermediate product. Acetylacetone was added, and the molar ratio of acetylacetone to Nb and Al was 2:1. The pH was adjusted to 5.5 with ammonia water, stirred at 70°C for 4 h, filtered, washed and dried, and heat-treated in air at 550°C for 3 h to form a third coating layer of niobium aluminosilicate nanocrystals with a thickness of 12 nm, thus obtaining the third intermediate product.

[0141] The third intermediate product was immersed in an aqueous solution containing 2 wt% PEDOT:PSS, stirred for 2 hours, filtered, and vacuum dried at 80°C to form a fourth coating layer of conductive polymer with a thickness of 10 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0142] Example 11

[0143] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0144] Take NCA (LiNi) 0.8 Co 0.15 Al 0.05 O2, D 50100g of Nb(OC2H5)5 (9 μm) was added to a 1L mixed solution of ethanol and water in a volume ratio of 8:2. Then, Nb(OC2H5)5, TEOS and Al(NO3)3·9H2O were added sequentially, with the molar ratio of Nb, Si and Al being 1.5:1:1. The total amount of metal salt (Nb(OC2H5)5 and Al(NO3)3·9H2O) was 1.0wt% of NCA. Citric acid was then added, with the molar ratio of citric acid to the total molar amount of Nb and Al in the metal salt being 1:1. The pH of the system was then adjusted to 5.0 with ammonia. The mixture was stirred at 60℃ for 3h, filtered and washed, and dried at 80℃ for 10h to obtain the precursor.

[0145] The precursor was mixed with LiOH·H2O (the total molar ratio of lithium salt to the aforementioned Nb and Al elements was 1.05:1), placed in a tube furnace, and then kept at 650℃ for 5 hours under a nitrogen atmosphere to obtain the first coating layer of the lithium-ionized niobium aluminosilicate amorphous phase with a thickness of 30 nm, thus obtaining the first intermediate product.

[0146] The first intermediate product was placed in a fluidized bed atomic layer deposition apparatus, and atomic layer deposition was performed at 180°C using NbCl5 and H2O as precursors. Cyclic deposition was carried out to make the thickness of the second niobium oxide coating layer 4 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0147] Example 12

[0148] One embodiment of the multi-coated modified cathode material of this application, the preparation method of the multi-coated modified cathode material of this embodiment is as follows:

[0149] 100g of NCM811 (D50 is 10μm) was placed in a fluidized bed atomic layer deposition apparatus and atomic layer deposition was performed at 150℃ using trimethylaluminum (TMA) and H2O as precursors. Cyclic deposition was carried out to make the thickness of the first alumina coating layer 3nm, and the first intermediate product was obtained.

[0150] The first intermediate product was transferred into a chemical vapor deposition reactor, and tetraethyl orthosilicate (TEOS) vapor (TEOS: 1.0 g / min) along with a carrier gas and an oxidizing gas (oxygen: 1000 sccm; nitrogen: 5000 sccm) was introduced at 520°C. Deposition was carried out for 40 min to form a second SiO2 coating layer with a thickness of 10 nm, thus obtaining the second intermediate product.

[0151] The second intermediate product was mixed with Al(NO3)3 and heat-treated at 650°C for 6 hours to form an alumina third coating layer with a thickness of 15 nm, thus obtaining the multi-coated modified cathode material described in this embodiment.

[0152] Comparative Example 1

[0153] This application provides a comparative example of a multi-coated modified cathode material. The preparation method of the multi-coated modified cathode material described in this comparative example is as follows: 100g of NCM811 (D50 is 10μm) is taken and dried in a vacuum at 150℃ for 12h without any coating treatment.

[0154] Comparative Example 2

[0155] This application provides a comparative example of a coated and modified cathode material. The difference between the preparation method of the coated and modified cathode material in this comparative example and that in Example 1 is that the first intermediate product is the coated and modified cathode material described in this comparative example.

[0156] Comparative Example 3

[0157] This application provides a comparative example of a coated and modified cathode material. The preparation method of the coated and modified cathode material described in this comparative example is as follows:

[0158] 100g of NCM811 (D50 of 10μm) was placed in a chemical vapor deposition reactor, and tetraethyl orthosilicate (TEOS) vapor (TEOS: 1.0 g / min) along with a carrier gas and an oxidizing gas (oxygen: 1000 sccm; nitrogen: 5000 sccm) was introduced at 520℃. Deposition was carried out for 40 min to form a SiO2 coating layer with a thickness of 10nm, thus obtaining the coated modified cathode material described in this comparative example.

[0159] Comparative Example 4

[0160] This application provides a comparative example of a coated and modified cathode material. The preparation method of the coated and modified cathode material described in this comparative example is as follows:

[0161] 100g of NCM811 (D50 10μm) was added to 800mL of a mixed solution of ethanol and deionized water in a volume ratio of 7:3. Then, Nb(OC2H5)5, TEOS, and Al(NO3)3·9H2O were added sequentially, with a molar ratio of Nb, Si, and Al of 1:2:1. The total metal salts (Nb(OC2H5)5 and Al(NO3)3·9H2O) were added at 0.8wt% of the NCM811 content. Finally, lemon... Citric acid, with a total molar ratio of citric acid to Nb and Al elements in the metal salt of 1.2:1, was used to adjust the pH of the system to 4.5. After stirring at 40°C for 2 hours, the mixture was heated to 60°C for slow hydrolysis and condensation for 1 hour, forming a film in situ on the NCM811 surface. The film was filtered, washed, dried at 80°C for 12 hours, and then kept at 700°C for 3 hours in air to obtain a niobium aluminosilicate coating layer with a thickness of 25 nm, thus obtaining the coated modified cathode material described in this comparative example.

[0162] Comparative Example 5

[0163] This application provides a comparative example of a coated and modified cathode material. The preparation method of the coated and modified cathode material described in this comparative example is as follows:

[0164] Take NCM90 (LiNi) 0.9 Co 0.05 Mn 0.05 O2, D 50 100g of lithium phosphate (8 μm) was immersed in a 0.1mol / L ammonium dihydrogen phosphate solution, dried, and heat-treated at 450℃ for 2h to form a lithium phosphate coating layer with a thickness of 15nm, thus obtaining the coated modified cathode material described in this comparative example.

[0165] Performance testing

[0166] The performance testing methods for the examples and comparative examples are as follows, and the test results are shown in Table 1.

[0167] Electrode preparation: The positive electrode active material (the coated modified positive electrode material in the examples and comparative examples), conductive agent SP, and binder PVDF were added to NMP at a mass ratio of 8:1:1 to form a slurry. The slurry was then coated onto the surface of aluminum foil with an areal density of 10 mg / cm³. 2 ;

[0168] CR2032 coin cells were used, with lithium foil as the negative electrode for the half-cell and glass fiber as the separator. The electrolyte consisted of a 1:1:1 volume ratio of EC, DMC, and DEC as organic solvents, and LiPF6 as the lithium salt with a concentration of 1 mol / L. The cycling test was conducted at 25°C over a voltage range of 2V to 4.3V. The test rate was 0.1 A·g for the first three cycles. -1 , followed by 0.5 A·g -1 .

[0169] Table 1

[0170]

[0171] As can be seen from the above performance test results, the multi-coated modified cathode materials in the embodiments of this application all have good specific capacity, initial coulombic efficiency and cycle stability, and their application range is significantly wider than that of the comparative examples.

[0172] Comparing the performance test results of Examples 2, 5, 8, and 11 in this application, it can be found that when N=2 and the second coating layer is a first material such as niobium aluminosilicate, the battery using this multi-coated modified cathode material exhibits significantly better cycle stability and a longer service life. Furthermore, comparing the performance test results of Examples 2, 8, and 5, it can be found that when N=2 and the second coating layer is a first material such as niobium aluminosilicate, and the first coating layer is a second or third material, the overall electrochemical performance of the multi-coated modified cathode material is significantly better.

[0173] Furthermore, the performance test results of the above embodiments show that when the coating layer includes three or four layers, the cycle stability of the multi-coated modified cathode material is significantly stronger and the overall performance is better.

[0174] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. A multi-coated modified cathode material, characterized in that, The multi-coated modified cathode material includes a core and a shell. The core includes a cathode active material, and the shell includes N coating layers, where N is an integer between 2 and 4. The shell includes a first coating layer and a second coating layer, and the first coating layer and the second coating layer are stacked sequentially from the inside to the outside along the radial direction of the core. The thickness of each coating layer is independently 1 nm to 50 nm. The first coating layer and the second coating layer each independently include one of the first material, the second material, the third material, and the fourth material, and the materials of the first coating layer and the second coating layer are different; The first material includes at least one of niobium aluminosilicate, niobium silicate, niobium aluminate, aluminosilicate, lithium-modified niobium aluminosilicate, lithium-modified niobium silicate, lithium-modified niobium aluminate, and lithium-modified aluminosilicate. The second material includes at least one of lithium oxyacid salts, phosphates, and conductive polymers; The third material includes at least one oxide, oxyfluoride, or nitrogen oxide selected from aluminum, niobium, titanium, zirconium, tungsten, and boron; The fourth material includes at least one of silicon oxide, silicon nitride, silicon oxynitride, and silicon carbide.

2. The multi-coated modified cathode material according to claim 1, characterized in that, At least one of the following conditions must be met: (1) The oxyacid salt of lithium includes at least one of lithium phosphate, lithium aluminate, and lithium borate; (2) The phosphate includes ammonium metaphosphate; (3) The conductive polymer includes poly(3,4-ethylenedioxythiophene):polystyrene sulfonate; (4) The third material includes at least one of alumina, niobium oxide, zirconium oxide, titanium oxide, and titanium oxynitride; (5) The general chemical formula of the silicon oxide is SiO x Where 0 < x ≤ 2; (6) The general chemical formula of the silicon nitride is SiN. y Where 0.7 < y < 1.2; (7) The silicon carbide is SiC; (8) The first material is at least one of nanocrystalline phase and amorphous phase.

3. The multi-coated modified cathode material according to claim 1, characterized in that, The thickness of the shell is 2nm~200nm.

4. The multi-coated modified cathode material according to claim 1, characterized in that, When N=2, the second coating layer includes the first material, and the first coating layer includes at least one of the second material, the third material, and the fourth material; Preferably, the first coating layer comprises at least one of the second material and the third material.

5. The multi-coated modified cathode material according to any one of claims 1 to 3, characterized in that, The shell layer further includes a third covering layer, and the second covering layer is located between the first covering layer and the third covering layer. The third covering layer includes any one of the first material, the second material, the third material, and the fourth material, and the materials of the third covering layer, the first covering layer, and the second covering layer are different.

6. The multi-coated modified cathode material according to claim 5, characterized in that, When N=3, the first coating layer includes a third material or a fourth material, the second coating layer includes a fourth material or a second material, and the third coating layer includes a first material; the materials of the first coating layer and the second coating layer are different.

7. The multi-coated modified cathode material according to claim 5, characterized in that, The shell layer further includes a fourth covering layer, the third covering layer is located between the second covering layer and the fourth covering layer, the third covering layer includes the first material, the fourth covering layer includes any one of the second material, the third material, and the fourth material, and the material of the fourth covering layer is different from the material of the first covering layer, the material of the second covering layer, and the material of the third covering layer; Preferably, when N=4, the first coating layer includes a third material, the second coating layer includes a fourth material, the third coating layer includes a first material, and the fourth coating layer includes a second material.

8. The multi-coated modified cathode material according to any one of claims 1 to 4, characterized in that, Each of the N coating layers is prepared independently using at least one of atomic layer deposition, chemical vapor deposition, chemical reaction, and chemical impregnation methods. Preferably, when the coating layer comprises a first material, it is prepared by a chemical reaction method; when the coating layer comprises a second material, it is prepared by at least one of chemical impregnation and atomic layer deposition; when the coating layer comprises a third material, it is prepared by atomic layer deposition; and when the coating layer comprises a fourth material, it is prepared by chemical vapor deposition.

9. A positive electrode sheet, characterized in that, The cathode material includes the multi-coated modified cathode material according to any one of claims 1 to 8.

10. A secondary battery, characterized in that, Includes the positive electrode sheet as described in claim 9.